Immune Responses to the Sexual Stages of Plasmodium falciparum Parasites - Kengne-Ouafo, Jonas A.; Sutherland, Colin J.; Binka, Fred N.; Awandare, Gordon A.; Urban, Britta C.; Dinko, Bismarck (Frontiers in Immunology, 2019)
Malaria infections remain a serious global health problem in the world, particularly among children and pregnant women in Sub-Saharan Africa. Moreover, malaria control and elimination is hampered by rapid development of resistance by the parasite and the vector to commonly used antimalarial drugs and insecticides, respectively. Therefore, vaccine-based strategies are sorely needed, including those designed to interrupt disease transmission. However, a prerequisite for such a vaccine strategy is the understanding of both the human and vector immune responses to parasite developmental stages involved in parasite transmission in both man and mosquito. Here, we review the naturally acquired humoral and cellular responses to sexual stages of the parasite while in the human host and the Anopheles vector. In addition, updates on current anti-gametocyte, anti-gamete and anti-mosquito transmission blocking vaccines are given. We conclude with our views on some important future directions of research into P. falciparum sexual stage immunity relevant to the search for the most appropriate transmission-blocking vaccine.